(untitled) (London Journal of Engineering Research, 2022)
This paper reviewed the advances and challenges of anaerobic biodigestion technology. The technology is an attractive waste to wealth strategy exploited to proffer solutions to the environmental, energy and agricultural needs. As reviewed, the process is generally considered to be slow and unstable due to strict nature of the anaerobes and difficult to operate. The advances in anaerobic digestion technology considered in this study are attributed to the diversity in bio-sourced feedstock, digester design and variability of process conditions. Thesehighly researchable areas were extensively reviewed. It was found that pretreatment of feedstock, substrate interaction with the novel inoculum and substrate combo which involves mixture of different classes of feedstock that ferment better together than separately due to their enriched microbial load as well as their nutritional requirements, are recent strategies exploited to improve anaerobic biodigestion process. In addition, research on thermal effect, alternating thermophilic, mesophilic and psychrophilic stages while evaluating the impacts of temperature, pH and pressure have been adequately investigated as reviewed. However, the process is challenged by poor biodigester design/configurations, the inhibitory episodes from antagonistic substrate combo and the offensive odor of the effluent on fertilizer application. The review on these challenges is necessary towards improving the process. On the whole, for improved biodigestion of substrates, these strategies such as pretreatment, co-digestion, etc. should be exploited. Specifically, pretreatment of feedstock facilitates biodigestion and improves the accessibility of the source carbon utilizable by the microbial community, and mixing sources (co-digestion), working together as substrates, provides several advantages that improves biogas yields, methane production, and various other benefits.